2019
DOI: 10.1016/j.micromeso.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

From amorphous to crystalline: Transformation of silica membranes into silicalite-1 (MFI) zeolite layers

Abstract: The transformation of microporous, amorphous silica membranes into b-oriented silicalite-1 (MFI) zeolite layers via in-situ crystallisation was investigated. The effect of synthesis parameters, such as the type and concentration of the silica precursor, crystallisation time and temperature, on the morphology of silicalite-1 (MFI) zeolite layers was studied. By optimizing these parameters, silicalite-1 zeolite layers were formed from the already-deposited silica layers, which promotes the crystallisation from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This secondary layer is due to the formation of crystals in the seed growth solution. Further deposition of secondary crystals on the already seeded support is also observed in the literature [31]. All membranes with high seed coating concentration (H) broke in the membrane module of the gas permeation set-up upon exposure to gases even without applying any thermal treatment because of the thick layer (almost 100 μm; see Fig.…”
Section: Membrane Fabrication and Its Characteristicssupporting
confidence: 75%
“…This secondary layer is due to the formation of crystals in the seed growth solution. Further deposition of secondary crystals on the already seeded support is also observed in the literature [31]. All membranes with high seed coating concentration (H) broke in the membrane module of the gas permeation set-up upon exposure to gases even without applying any thermal treatment because of the thick layer (almost 100 μm; see Fig.…”
Section: Membrane Fabrication and Its Characteristicssupporting
confidence: 75%
“…It is well known that in the structure of MFI zeolite membranes, the sinusoidal channel (0.51 × 0.55 nm, approximately circular section) parallel to the a-axis and the straight channel (0.53 × 0.56 nm, approximately elliptical cross section) parallel to the b-axis are connected [17], and a tortuous path exists along the c-axis direction as shown in Figure 1. A previous study [18] has shown that when tetrapropylammonium hydroxide (TPAOH) is used as a structure-directing agent (SDA), the MFI grains have a characteristic coffin shape and the threedimensional size is consistently longer along the caxis and smaller along the b-axis (Lc > La > Lb).…”
Section: Figure 1 Hydrothermal Synthesis Of Mfi Zeolitesmentioning
confidence: 99%
“…The sacrificial silica layers for the secondary growth of zeolite MFI (47)(48)(49) were prepared on top of porous silica supports by using 50-nm Stöber silica nanoparticles or mesoporous silica layers. Fifty-nanometer Stöber silica nanoparticles were deposited on porous silica supports with manual rubbing, followed by a heat treatment at 450°C for 6 hours.…”
Section: Fabrication Of Porous Supportsmentioning
confidence: 99%